3x-6=-8x+6+7x

Simple and best practice solution for 3x-6=-8x+6+7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6=-8x+6+7x equation:


Simplifying
3x + -6 = -8x + 6 + 7x

Reorder the terms:
-6 + 3x = -8x + 6 + 7x

Reorder the terms:
-6 + 3x = 6 + -8x + 7x

Combine like terms: -8x + 7x = -1x
-6 + 3x = 6 + -1x

Solving
-6 + 3x = 6 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-6 + 3x + x = 6 + -1x + x

Combine like terms: 3x + x = 4x
-6 + 4x = 6 + -1x + x

Combine like terms: -1x + x = 0
-6 + 4x = 6 + 0
-6 + 4x = 6

Add '6' to each side of the equation.
-6 + 6 + 4x = 6 + 6

Combine like terms: -6 + 6 = 0
0 + 4x = 6 + 6
4x = 6 + 6

Combine like terms: 6 + 6 = 12
4x = 12

Divide each side by '4'.
x = 3

Simplifying
x = 3

See similar equations:

| 14=-4(y-3)-3 | | 2/19=19y | | -(3y+3)-(-2y-6)=-1 | | 1/3(10x-6)=8 | | 6p-32-35=5 | | x+5=56 | | 3x^2+14x+31=0 | | x-2/2x^2-9x+10=0 | | -4x^2-11x-6=0 | | 1/2(c+8)=1/4c | | 2x-24=6x | | 8x+82=3x+2 | | 6ln(x^2-3)-7=12.2 | | 7+18r-3=6r+64-3r | | -12x-114=5x+11+8x | | -x^2-x+2=3x^2+10x+8 | | 8(y-3)=3y-59 | | 6(m-1/9)=55/12 | | x-4y=-25 | | 18-c+36=49 | | x+(x+35)+(2x-39)=592 | | 2(4d-6)=5d+12 | | x+13+1=44 | | 4k+4=2(k+5) | | 2/3x+1/9y=-19/27 | | 2.5x+10=1.5+17 | | 2r+4r=12 | | x+(x+100000)=600000000 | | 4y-19-y=-59+y | | -6-8(x+7)=-32-2x | | z/8=-6 | | -7x+26=6x |

Equations solver categories